BUILDING THE RESILIENCE OF NARCOTICS CASE PRISONERS IN CLASS IIB SEKAYU PRISON - Kamil, Taufiq; Butar Butar, Herry Fernandes (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Resilience, as the ability to recover from stress and trauma, is considered essential in supporting the rehabilitation process of inmates. This study aims to explore how resilience can be built among inmates convicted of narcotic offenses in Lapas Kelas IIB Sekayu and to identify the challenges faced in this process. The study employs a qualitative method, utilizing in-depth interviews, observations, and document analysis for data collection. The first finding shows that the rehabilitation program in Lapas Kelas IIB Sekayu involves various aspects focused on the mental, emotional, and social development of inmates, with support from prison officers and families playing a key role in fostering resilience. The second finding identifies the main challenges in building inmate resilience, including social stigma, psychological pressure, and limited supporting facilities within the prison. By developing resilience, inmates can be better prepared for life after release and reduce the risk of reoffending. Keywords: Resilience; Inmates; Narcotics; Rehabilitation; Lapas Kelas IIB Sekayu